How Do Students Thinking Processes in Solving Originality and Elaboration Problems of Mathematical Creative Thinking Based on Brain Domination? - Bayu Sukmaangara; Sri Tirto Madawistama (EduMa: Mathematics education learning and teaching, 2023)
Thought processes and brain dominance can be applied in the field of education because of the linkages between neuroscience, psychology, and education. The thinking process of students can assist teachers in planning the learning process, while brain dominance is an important factor in student performance so it is important to know students' thinking processes based on brain dominance in the learning process. This research aims to describe students’ thinking processes in solving originality and elaboration problems on mathematical creative thinking based on brain dominance. The research method used is qualitative with a descriptive exploratory approach. The instrument used is a matter of mathematical creative thinking that meet the indicators of originality and elaboration, brain dominance tests, and unstructured interviews. The Subject selected research was 3 subjects, namely 1 subject dominated by the left brain, 1 subject dominated by a balanced brain, and 1 subject dominated by the right brain. The subject is a class IX student of SMPN 1 Kota Tasikmalaya. The result of the research is that the thinking process of students in solving originality and elaboration questions creative thinking mathematically based on brain dominance in solving problems cannot be separated from the function of the right and left hemispheres. The thinking process of students in solving problems shows that students use the characteristics of the function of the hemispheres of the brain according to the dominance of the student's brain